1984
DOI: 10.1093/oxfordjournals.aje.a113891
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Questionnaire-Derived Historical Dietary Information and Temporal Stability of Food Habits in Individuals

Abstract: Thirty-four males and 45 females who participated in household surveys 15 or 25 years earlier in rural Denmark were interviewed in 1982 about present and past food habits. Comparison of the information from the survey and the two interviews indicates that recall of past diet is strongly influenced by present dietary habits. As the relative classification of individuals according to their food habits appears to have changed little over time, information on current diet, perhaps supplemented by information on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(55 citation statements)
references
References 0 publications
5
49
1
Order By: Relevance
“…They found a correlation of 0.28, as did Byers et al (1983) for milk. Jensen et al (1984) found higher values over a 15±25 y period for whole milk (0.42) as well as for milk products (0.37).…”
Section: Trackingmentioning
confidence: 86%
See 2 more Smart Citations
“…They found a correlation of 0.28, as did Byers et al (1983) for milk. Jensen et al (1984) found higher values over a 15±25 y period for whole milk (0.42) as well as for milk products (0.37).…”
Section: Trackingmentioning
confidence: 86%
“…Medicine use might increase with increasing age in a middle-aged population. The longitudinal development of dairy intake was examined by reports of Byers et al (1983) and Jensen et al (1984). These studies were based on a 15±25 y time period in 175 and 79 middle-aged males and females with a median age of 42 and 37 y respectively.…”
Section: Longitudinal Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current dietary habits are found to provide as good information about the past diet as evaluating the habits by retrospective methods (Jensen et al, 1984). On this basis, we decided to get information about the diet from the time before the disease was manifest.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is acknowledged that reproducibility itself does not demonstrate the validity of dietary memories. The influence of current diet on past diet reporting has been well documented (45)(46)(47)(48) and in the case of the Lifetime Diet Questionnaire it could be argued that the questionnaire's reproducibility may be due to participants consistently reporting similar versions of their current dietary intake for all periods and across both questionnaire time points. However, dietary patterns have been shown to change over time (21,26,49) and so it could be expected that if the questionnaire was validly assessing lifetime memory, there would be stronger associations between two recalls of the same dietary period than between that life period and a later life period.…”
Section: Discussionmentioning
confidence: 99%